Gemstone spectral imaging: determination of CT to ED conversion curves for radiotherapy treatment planning. (6th September 2013) - Yagi, Masashi; Ueguchi, Takashi; Koizumi, Masahiko; Ogata, Toshiyuki; Yamada, Sachiko; Takahashi, Yutaka; Sumida, Iori; Akino, Yuichi; Konishi, Koji; Isohashi, Fumiaki; Tomiyama, Noriyuki; Yoshioka, Yasuo; et al.
Abstract : The monochromatic images acquired by Gemstone spectral imaging (GSI) mode on the GE CT750 HD theoretically determines the computed tomography (CT) number more accurately than that of conventional scanner. Using the former, the CT number is calculated from (synthesized) monoenergetic X‐ray data. We reasoned that the monochromatic image might be applied to radiotherapy treatment planning (RTP) to calculate dose distribution more accurately. Our goal here was to provide CT to electron density (ED) conversion curves with monochromatic images for RTP. Therefore, we assessed the reproducibility of CT numbers, an important factor on quality assurance, over short and long time periods for different substances at varying energy. CT number difference between measured and theoretical value was investigated. The scanner provided sufficient reproducibility of CT numbers for dose calculation over short and long time periods. The CT numbers of monochromatic images produced by this scanner had reasonable values for dose calculation. The CT to ED conversion curve becomes linear with respect to the relationship between CT numbers and EDs as the energy increases. We conclude that monochromatic imaging from a fast switching system can be applied for the dose calculation, keeping Hounsfield units (HU) stability. PACS numbers: 87.55.‐x, 87.55.ne, 87.57.N‐, 87.59.bd